THE FACTORS AFFECTING THE WELFARE OF STREET VENDORS IN INDONESIA - Handoyo, Eko; Wijayanti, Tutik (PLANNING MALAYSIA, 2021)
This study aimed to examine how the welfare of street vendors is influenced by education, financial capital, geographical distance, and social networks. A mixedmethod approach that combines both quantitative and qualitative methods was used. The results showed that the welfare of street vendors is at a low level and is simultaneously influenced by education, financial capital, geographical distance, and social networks with a determination value of r-square (r2) of 0.783 or 78.3%. However, there is a need for further and in depth studies on the influence of geographical factors and social networks on the welfare of street vendors, especially on geographical factors with a significant influence on welfare.